Analytical basis of the contracting enterprise's activity in the modern digital environment - Bondar, А.A.; Pokolenko, V.O.; Pilipchuk, O.D.; Khalilov, Arzu (Ways to Improve Construction Efficiency, 2021)
In the article on the basis of the former general-methodical basis where the methodology of construction developer and digital administration by construction organizations is combined; scientific and applied bases of VIM-technologies; "Geometric econometrics"; modern methods of formalized modeling and adjustment of the cycle of development projects; the latest approaches to the formation of organizational structures for the management of construction production with the involvement of digital technologies. The methodological basis of the study was based on a productive combination of visual and graphical capabilities of BIM-technology, digital control technologies, methods of graph-analytical visualization (provided through the use of "geometric econometrics"). The resulting methodological apparatus allows the use of BIM-technologies in the organization of construction in fundamentally new positions - not only as a means of graph-analytical structuring of physical volumes of contract work, but, above all, as a modern basis for variable organizational and technological modeling of works and stages of construction. project and as a tool for managing the cycle and environment of the development project. It is substantiated and proved that when forming the analytical basis of the construction enterprise in modern digital space it is expedient to take into account the vector of improvement of management models in the direction from single-purpose to multi-purpose, from deterministic to deterministic-stochastic, from worc-arc model (robot-arc). to the model of the synthetic type “worc & matrix” “work & top”. The successful operation and development of construction organizations participating in projects in the digital environment requires a sound approach to the formation of their competitive strategy as executors. The article highlights that the concept of competitive strategy of the contractor is a set of rules and techniques that should guide the construction organization, ready for change in its activities through the involvement of digital management format: integral elements of the process of digital transformation in construction are changes in activities of construction organizations, which consist in a full-scale digital transformation based on the company's digital development strategy. Implementing the measures envisaged by the digital strategy requires an integrated approach that includes the company's development in various areas, but understanding the trends of the digital environment and construction market will allow companies to rationally use existing digital potential and effectively identify ways to further digital development of construction companies.